Validitas dan Kepraktisan Modul Resiliensi Berbasis Persuasif Playing Pada Siswa Tunagrahita - Balong, Fiqrul Khazanah; Latif, Suciani; Fitri, Qawiyyan; Harum, Akhmad (Indonesian Journal of School Counseling: Theory, Application, and Development, 2025)
This study aims to develop a module as a medium for increasing resiliencefor children with intellectual disabilities in one of the SLBC schools in Makassar usingthe ADDIE development model. The purpose of this study was to test the validity andpracticality of the module. The analysis method used was descriptive qualitative andquantitative. The results showed that the persuasive play-based module wasdeveloped in print using the Procreate application. This module was validated withan average score of 94% (material) and 96.25% (media), indicating a high level ofvalidity. In addition, the module's practicality received an average score of 94.25%based on the principal's assessment and small group trials, indicating that themodule is very practical to use in increasing the resilience of children withintellectual disabilities.